Analisis Akad Mudharabah di Perbankan Syariah - Hidayati Nasrah (JURNAL AL-IQTISHAD, 2015)
This study tried  to  see  mudharabah  practices  by  Islamic banks, whether the implementation  and practice  mudharabah  is in accordance with  Islamic Shari'a. In this study  also  described  the practice of  gift-giving  in early  when customers  deposit  funds  in Islamic banks. Practices  carried out  by the  Islamic Bank  raises  a lot of  criticism from  people who think  that  Islamic banks  are notdifferent from conventional banks, only  the title  that  sharia. The study was conducted  with descriptive methods,  compare  theory  derived  from the study ofliterature  with the practice  in the field. The study found  there are many  Islamic banking  practices  in the implementation of  mudharabah,  particularly in terms ofcapital ownership  status  and responsibility  to bear  the risk  violate  what  isoutlined in the  Shariah. In  terms of  gift-giving  at the beginning, it was found  thatthe gift  made  Islamic banks  with  a specific purpose,  grant  can not be  justified  inShari’a.